Grain color formation and analysis of correlated genes by metabolome and transcriptome in different wheat lines at maturity - Li, Li; Zhang, Hui; Liu, Junna; Huang, Tingzhi; Zhang, Xuesong; Xie, Heng; Guo, Yirui; Wang, Qianchao; Zhang, Ping; Qin, Peng (Frontiers in Nutrition, 2023)
Colored wheat has been recognized broadly for its nutritional value because of its natural content of the colorant anthocyanin. To investigate the reasons for the formation of the wheat grain color at maturity, metabolomic and transcriptomic analyses were performed on three different grain colors of wheat. Through metabolome analysis, 628 metabolites were identified. Of the 102 flavonoids, there are 9 kinds of anthocyanins related to color formation, mainly cyanidin and peonidin, and their metabolite content was the lowest in white-grain wheat. Among the genes associated with color formation, the structural gene TraesCS2D02G392900 in F3H with the bHLH transcription factor could elucidate the origin of wheat coloration. Multi-omics analysis showed that color formation is mainly influenced by the regulation of genes affecting anthocyanin and related synthesis. The results of this study may provide a theoretical basis for grain color formation at maturity and the nutritional and product development potential of colored wheat lines.